Optimization of Solar Panel Tilt for Enhanced Electrical Power Output based on Solar Radiation Variations in Cilacap - Soolany, Christian; Pangestu, Nur Aji Bangkit Barkah; Waluyo, Didi Zinedine; Sutisna, Setya Permana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2026)
The performance of photovoltaic (PV) systems in tropical regions such as Indonesia is strongly influenced by the panel tilt angle, which determines the amount of solar radiation captured. An inappropriate orientation can cause substantial energy losses and reduce overall system efficiency. This study experimentally investigates the optimal tilt angle for a 100 Wp monocrystalline solar panel to maximize power generation in Cilacap, Indonesia (7.6252° S, 109.1134° E). The experiment was conducted in November 2024 under clear sky conditions, with hourly measurements of solar irradiance, and electrical power output at three tilt angles: 30°, 45°, and 60°. The results show that the 30° tilt angle consistently produced the highest performance, reaching a maximum power output of 194.5 W and an efficiency of 19.5% under peak solar irradiance of 1030 W/m² at 11:00 WIB. In contrast, the 60° configuration exhibited the lowest output, particularly during the afternoon period. It is concluded that a fixed tilt angle of 30° provides the most effective configuration for photovoltaic installations in Cilacap, aligning with the solar geometry of tropical regions.